Predictors of infarction and outcomes in capsular warning syndrome: a retrospective observational study - Guo, Rui-xi; Wang, Tao (Frontiers in Neurology, 2025)
BackgroundCapsular warning syndrome (CWS), a rare subtype of transient ischemic attack, is associated with a high risk of progression to acute cerebral infarction. However, predictive factors for infarction and determinants of functional outcome remain inadequately defined.MethodsIn this retrospective study, we analyzed 89 CWS patients admitted between January 2021 and December 2024. Clinical, laboratory, imaging, and treatment data were collected. Patients were stratified into infarcted and non-infarcted groups based on DWI findings. Infarcted patients were followed for 90 days, with outcomes assessed using the modified Rankin Scale (mRS). LASSO regression was used for variable selection, followed by multivariable logistic regression to identify independent predictors of infarction and favorable 90-day outcomes (mRS 0–2).ResultsOf 89 patients, 57 (64%) experienced infarctions. Independent predictors included elevated platelet count (OR = 1.02, 95% CI: 1.01–1.04, p = 0.002), higher NIHSS score (OR = 1.96, 95% CI: 1.25–3.55, p = 0.011), higher ABCD2 score (OR = 1.86, 95% CI: 1.04–3.60, p = 0.047), intracranial atherosclerosis (OR = 10.5, 95% CI: 1.54–99.0, p = 0.024), and male sex (OR = 5.57, 95% CI: 1.32–27.9, p = 0.024). Among 57 infarcted patients, tirofiban infusion was the only independent predictor of favorable outcome (OR = 0.01, CI: 0.00–0.07, p < 0.001).ConclusionIn CWS, infarction risk is independently associated with platelet count, clinical severity, vascular pathology, and sex. Tirofiban may improve short-term outcomes in infarcted patients. Prospective multicenter studies are needed to validate these findings.